The encyclopedia of leadership a practical guide to popular leadership theories and techniques - Hiebert, Murray 1943-; Klatt, Bruce; Gale Group (New York McGraw-Hill, 2001)
Comprehensive reference guide to over 200 of the most important business leadership principles, theories, tools, and techniques. Each entry features a brief, one-page summary of an influential theory or tool, followed by a worksheet or exercise. A comprehensive guide to the leadership principles, theories, tools and techniques in the organizational world. It helps to find brief summaries of various important leadership ideas including: the basic competencies and practices of successful leaders; finding the best leadership technique for the situation; and, leading groups and teams.
Section 1. Foundational concepts -- Section 2. Tools for big-picture thinking -- Section 3. Tools for strategic thinking -- Section 4. Tools for designing productive processes and organization -- Section 5. Tools for leading change -- Section 6. Tools for critical thinking and innovation -- Section 7. Tools for problem solving, decision making, and quality -- Section 8. Tools for communication -- Section 9. Tools for leading and influencing others -- Section 10. Tools for leading teams and groups -- Section 11. Tools for leading meetings -- Section 12. Tools for leading relationships --Section 13. Tools for leading performance -- Section 14. Tools for learning -- Section 15. Tools for taking care of yourself.
Electronic reproduction.
Keywords: Leadership -- Handbooks, manuals, etc; Electronic books